Internship in the environment operations center in the Greater Mekong Subregion countries - Wu, Jian; Dimmitt, Nicholas J.; Neal, Mark W.; Winai Wongsurawat; Government of People{u2019}s Republic of China (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
Environment protection and sustainable development have become worldwide concerns. In these fields, the regional or international organization has played an increasingly important role. How do these institutions exercise their influences? What will their institutional structures look like? Through my three-month hands-on internship experience in the Environment Operation Center in the Greater Mekong Subregion (EOC), I have gained some tangible idea of the above questions. In this internship report, general information of the EOC is given first. Then, I discuss the major concerns in the EOC{u2019}s institutionalization process. Finally, I will share the lessons learned from this internship work.
A project submitted in partial fulfillment of the requirements for the degree of Master of Business Management in International Public Management, School of Management
Project (M.B.A.) - Asian Institute of Technology, 2008
Keywords: Environmental protection -- Mekong River Delta; Sustainable development -- Mekong River Delta